Quo vadis – poziomy recepcji w Bułgarii - Nikołaj Spasow Daskałow (Postscriptum Polonistyczne)
The article deals with the different levels of reception of Henryk Sienkiewicz’s ‘Christian epic’ Quo Vadis in Bulgaria. It focuses on an issue which is of exceptional interest in the Bulgarian context: Quo Vadis is amongst the most widely read and translated novels of the world classics and yet has not been integrated in the ‘repertoire’ of Bulgarian literary science and thought. According to some research statistics its scale of reception is phenomenological, but it has not impacted our literary tradition of novel writing. This is a paradox, which can only be explained as a result of the specificity of the intellectual and religious experience of the Bulgarian people.